Branch Retinal Vein Occlusion with Vitreous Hemorrhage Identified During Intraoperative Vitrectomy - Nafila Mahida Sukmono; Ramzi Amin (International Journal of Retina, 2018)
Introduction Retinal vein occlusion is the largest group of retinal blood vessels after diabetic retinopathy. Occlusion occurring in the retinal vein is divided into central retinal vein occlusion (CRVO) occlusion and branch retinal vein occlusion (BRVO) occlusion. The Beijing Eye Study, reported a higher incidence of BRVO than CRVO, where 10-year incidents for BRVO were 1.6 per 100 subjects, and CRVO was only 0.3% 100 subjects.1 To report a case of Branch Retinal Vein Occlusion with vitreous hemorrhage identified during intraoperative vitrectomy Method: A 49-year-old woman with a history of 15 years of hypertension had right eye vision complaints, increasingly blurred since last 2 months. The right eye visual acuity 2/60 cannot be corrected and left eye 6/30 cannot be corrected. The posterior segment on right eye is difficult to assess. USG B-Scan right eye found vitreous echospike appearance of vitreous bleeding. We manage with vitrectomy and during intraoperative we identified bleeding and ghost vessel in superotemporal area. Bleeding in the superotemporal quadrant is done by photocoagulation laser action. Results: First day postoperative there was increased in visual acuity to 6/60 with a posterior segment that could be assessed, obtained tortous blood vessels, slight bleeding and ghost vessel in the superotemporal area with laser injury. Conclusion: In this case report, patients with BRVO with complications of vitreous hemorrhage performed vitrectomy with additional endolaser in the ischemic area. The result of this action of visual acuity improvement in patient.